Acceptance of Islamic Banking among non-muslims in Malaysia - Stellia, Djapri (Universiti Malaysia Sarawak (UNIMAS), 2013)
IslamiC banking has been almost three decades when the first Islamic bank makes ,its debut in Malaysia. Islamic banks have to face stiff competition, especially with conventional banks which have longer history than Islamic banks. thus, it is important for the Islamic banks to know the awareness, understanding, attitudes and banking selection criteria of Malaysians, especially non-Muslims towards it. In Malaysia, we have roughly 40% of the population belongs to non-Muslims and hence non-Muslims market is respectively important to Islamic ban0 The purpose of this research is to examine the level of awareness, understanding, attitudes and banking selection criteria towards the acceptance of Islamic banking among non-Muslims. A total of 384 respondents from Sibu are chosen for the purpose of this study. For the analysis, Pearson moment product correlation and multiple linear regressions were adopted to analyze the results. The results indicated that the awareness, understanding, attitudes, banking selection criteria do have positive relationship with the acceptance towards Islamic banking. This study also provides implications for the Islamic bankers to attract non-Muslims customers and recommendations for future research in Islamic banking.